Connexin-Mediated Functional and Metabolic Coupling Between Astrocytes and Neurons - Mayorquin, Lady C.; Rodriguez, Andrea V.; Sutachan, Jhon-Jairo; Albarracín, Sonia L. (Frontiers in Molecular Neuroscience, 2018)
The central nervous system requires sophisticated regulation of neuronal activity. This modulation is partly accomplished by non-neuronal cells, characterized by the presence of transmembrane gap junctions and hemichannels. This allows small molecule diffusion to guarantee neuronal synaptic activity and plasticity. Astrocytes are metabolically and functionally coupled to neurons by the uptake, binding, and recycling of neurotransmitters. In addition, astrocytes release metabolites, such as glutamate, glutamine, D-serine, ATP, and lactate, regulating synaptic activity and plasticity by pre- and postsynaptic mechanisms. Uncoupling neuroglial communication leads to alterations in synaptic transmission that can be detrimental to neuronal circuit function and behavior. Therefore, understanding the pathways and mechanisms involved in this intercellular communication is fundamental for the search of new targets that can be used for several neurological disease treatments. This review will focus on molecular mechanisms mediating physiological and pathological coupling between astrocytes and neurons through gap junctions and hemichannels.